Effects of naringin on oxidative stress, inflammation, some reproductive parameters, and apoptosis in acrylamide‐induced testis toxicity in rat - Sengul, Emin; Gelen, Volkan; Yildirim, Serkan; Cinar, İrfan; Aksu, Emrah Hicazi (Wiley, 2023)
Abstract Acrylamide (ACR) is used in many fields such as cosmetics, paper, and textile industries. It also occurs at very high temperatures in some foods. Gonadotoxic effects of ACR have been found in experimental animals. Many studies use flavonoids to prevent the reproductive side effects of ACR. Naringin (NA) is a flavonoid and it has been determined by studies that it has no toxic effect on tissues. In our study, we aimed to determine the protective effect of NA against the damage of ACR on testicular tissue and the reproductive system in rats. In our study, 50 Spraque Dawley male rats weighing 220‐250 grams were used. Control: Only intragastric saline was administered for 10 days. ACR: Animals received ACR (40 mg/kg, intraperitoneally) for 10 days. NA50+ACR: Animals were given NA for 10 days and each NA was one hour after the administration of ACR. NA100+ACR: Animals received NA for 10 days and one hour after each NA was given ACR. NA100: Animals were given NA for 10 days. At the end of the applications, the rats were euthanized by cervical dislocation under anesthesia. Serum FSH, LH, and Dihydrotestosterone levels were compared between the groups. In addition, oxidative stress, inflammation, expression of some reproductive enzymes, and apoptosis markers were determined in testicular tissues. When these parameters were compared between groups, ACR induced testicular dysfunction and tissue damage in rats. We determined that only the NA application did not cause tissue damage. and the administration of NA along with ACR significantly reduced ACR‐induced testis toxicity.
Keywords: Male; Flavonoids; Inflammation; Acrylamide; Reproduction; Apoptosis; Antioxidants; Rats; Oxidative Stress; Testis; Animals; 3. Good health